2016
DOI: 10.1103/physrevd.94.043513
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of solitonic core mergers in ultralight axion dark matter cosmologies

Abstract: Using three-dimensional simulations, we study the dynamics and final structure of merging solitonic cores predicted to form in ultra-light axion dark matter halos. The classical, Newtonian equations of motion of a self-gravitating scalar field are described by the Schrödinger-Poisson equations. We investigate mergers of ground state (boson star) configurations with varying mass ratios, relative phases, orbital angular momenta and initial separation with the primary goal to understand the mass loss of the emerg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

34
362
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 324 publications
(397 citation statements)
references
References 46 publications
(81 reference statements)
34
362
1
Order By: Relevance
“…Comparing the initial and final masses of merging cores, [23] find a universal behavior of the core mass loss in mergers that depends nearly entirely on the mass ratio. Implementing this relation in a semianalytic model (SAM) for galaxy formation, [27] studies the effects of the core on the substructure of Milky way-sized FDM halos.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing the initial and final masses of merging cores, [23] find a universal behavior of the core mass loss in mergers that depends nearly entirely on the mass ratio. Implementing this relation in a semianalytic model (SAM) for galaxy formation, [27] studies the effects of the core on the substructure of Milky way-sized FDM halos.…”
Section: Introductionmentioning
confidence: 99%
“…Removing any residual effects of the scaling symmetry by constructing and analyzing scale invariant quantities, [23] were unable to reproduce this relation in simulations of solitonic core mergers. Furthermore, the model of [11] does not account for the combined evolution of M c and M h by halo mergers after the initial collapse of density perturbations which is known to be an important ingredient in hierarchical structure formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that the SFDM can explain the contradictory behaviors of DM in collisions of galaxy clusters [90][91][92][93][94]. For a fast collision as observed in the Bullet cluster two dark matter halos pass each other in a solitonlike way, while for a slow collision as observed in the Abell 520 the halos merge due to the wave nature of the SFDM.…”
mentioning
confidence: 99%